Forest roads act as habitat corridors for Populus tremuloides in the boreal forest of eastern Canada - Marchais, Mathilde; Arseneault, Dominique; Bergeron, Yves (Frontiers in Ecology and Evolution, 2024)
Edge habitats resulting from the construction and maintenance of forest roads favour pioneer, shadeintolerant and disturbance-adapted plant species. The effect of roads on the spread of non-native species has been frequently studied, but few studies have focused upon their effects on native tree species. We studied the effect of forest roads on the expansion dynamics of trembling aspen (Populus tremuloides Michx.) in a boreal forest landscape of eastern Canada. We determined whether roads act as a habitat and dispersal corridor for trembling aspen, and whether populations that established along roads act as a starting point for aspen expansion into adjacent stands. We evaluated the effect of forest roads on the distribution of trembling aspen by surveying the vegetation along 694 km of roads. In 19 stands, we compared the density and age of individuals in 100 m transects established parallel and perpendicular to roads, to determine the role of roads. Trembling aspen is abundant along the forest road network. Forest roads act sometimes as habitat corridors for trembling aspen, but their effects on its density extend only over a short distance (10 m) on each side of the roads. The forest roads did not act as a starting point for the expansion of trembling aspen into adjacent stands. Forest roads are particularly favourable habitats for trembling aspen. Although roads did not act as a starting point for aspen dispersal away from roads, these habitats would be vulnerable to invasion following a disturbance that would reduce the thickness of the organic layer.